Insights into surgical trials: methodological challenges and solutions - Dörr-Harim, Colette; Bruckner, Thomas; Diener, Markus K.; Knebel, Phillip (Langenbeck's archives of surgery, 2014)
Novel surgical methods and procedures used to be introduced by experts and were established depending on the corresponding success that was noted. Surgical trials representing evidence level 1b were and still are called into question for different reasons. Prospective randomized controlled trials comparing various surgical strategies that were conducted over the past 11 years in the clinical trial unit in the department of general, visceral, and transplantation surgery of the University of Heidelberg pointed out problems as well as possible solutions for surgical trials’ characteristics.